Multicenter Retrospective Review of Ketamine Use in the ICU. (10th February 2022) - Groth, Christine M.; Droege, Christopher A.; Connor, Kathryn A.; Kaukeinen, Kimberly; Acquisto, Nicole M.; Chui, Sai Ho J.; Cucci, Michaelia D.; Dixit, Deepali; Flannery, Alexander H.; Gustafson, Kyle A.; Glass, Nina E.; Horng, Helen; et al.
Abstract : IMPORTANCE: The response of ICU patients to continuously infused ketamine when it is used for analgesia and/or sedation remains poorly established. OBJECTIVES: To describe continuous infusion (CI) ketamine use in critically ill patients, including indications, dose and duration, adverse effects, patient outcomes, time in goal pain/sedation score range, exposure to analgesics/sedatives, and delirium. DESIGN, SETTING, AND PARTICIPANTS: Multicenter, retrospective, observational study from twenty-five diverse institutions in the United States. Patients receiving CI ketamine between January 2014 and December 2017. MAIN OUTCOMES AND MEASURES: Chart review evaluating institutional and patient demographics, ketamine indication, dose, administration, and adverse effects. Pain/sedation scores, cumulative doses of sedatives and analgesics, and delirium screenings in the 24 hours prior to ketamine were compared with those at 0–24 hours and 25–48 hours after. RESULTS: A total of 390 patients were included (median age, 54.5 yr; interquartile range, 39–65 yr; 61% males). Primary ICU types were medical (35.3%), surgical (23.3%), and trauma (17.7%). Most common indications were analgesia/sedation ( n = 357, 91.5%). Starting doses were 0.2 mg/kg/hr (0.1–0.5 mg/kg/hr) and continued for 1.6 days (0.6–2.9 d). Hemodynamics in the first 4 hours after ketamine were variable (hypertension 24.0%, hypotension 23.5%, tachycardia 19.5%, bradycardia 2.3%); other adverse effects were minimal. Compared with 24 hours prior, there was a significant increase in proportion of time spent within goal pain score after ketamine initiation (24 hr prior: 68.9% [66.7–72.6%], 0–24 hr: 78.6% [74.3–82.5%], 25–48 hr: 80.3% [74.6–84.3%]; p < 0.001) and time spent within goal sedation score (24 hr prior: 57.1% [52.5–60.0%], 0–24 hr: 64.1% [60.7–67.2%], 25–48 hr: 68.9% [65.5–79.5%]; p < 0.001). There was also a significant reduction in IV morphine (mg) equivalents (24 hr prior: 120 [25–400], 0–24 hr: 118 [10–363], 25–48 hr: 80 [5–328]; p < 0.005), midazolam (mg) equivalents (24 hr prior: 11 [4–67], 0–24 hr: 6 [0–68], 25–48 hr: 3 [0–57]; p < 0.001), propofol (mg) (24 hr prior: 942 [223–4, 018], 0–24 hr: 160 [0–2, 776], 25–48 hr: 0 [0–1, 859]; p < 0.001), and dexmedetomidine (µg) (24 hr prior: 1, 025 [276–1, 925], 0–24 hr: 285 [0–1, 283], 25–48 hr: 0 [0–826]; p < 0.001). There was no difference in proportion of time spent positive for delirium (24 hr prior: 43.0% [17.0–47.0%], 0–24 hr: 39.5% [27.0–43.8%], 25–48 hr: 0% [0–43.7%]; p = 0.233). Limitations to these data include lack of a comparator group, potential for confounders and selection bias, and varying pain and sedation practices that may have changed since completion of the study. CONCLUSIONS AND RELEVANCE: There is variability in the use of CI ketamine. Hemodynamic instability was the most common adverse effect. In the 48 hours after ketamine initiation compared with the 24 hours prior, proportion of time spent in goal pain/sedation score range increased and exposure to other analgesics/sedatives decreased.